2002
DOI: 10.1111/j.1752-0606.2002.tb00365.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting 2‐year Marital Satisfaction From Partners' Discussion of Their Marriage Checkup

Abstract: This study tested whether the observed marital interactions of partners following a marriage checkup predicted marital satisfaction 2 years later. In addition, this study examined whether recommendations to pursue therapy predicted subsequent treatment seeking and whether changes in marital distress following the checkup remained stable over 2 years. Results suggest that the affective tone of a couple's interaction predicts later marital satisfaction. Further, receiving a treatment recommendation predicted sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 8 publications
(10 reference statements)
0
18
0
1
Order By: Relevance
“…Finally, this study was limited to assessing couples only 60 days after taking RELATE, and the long‐term effects on couple relationships are unknown. However, findings from Gee, Scott, Castellani, and Cordova (2002) suggest that the positive effects of participation in brief relationship evaluation assessments such as RELATE may be maintained for up to 2 years, but follow‐up studies should be done before drawing such conclusions about RELATE or other PAQs.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this study was limited to assessing couples only 60 days after taking RELATE, and the long‐term effects on couple relationships are unknown. However, findings from Gee, Scott, Castellani, and Cordova (2002) suggest that the positive effects of participation in brief relationship evaluation assessments such as RELATE may be maintained for up to 2 years, but follow‐up studies should be done before drawing such conclusions about RELATE or other PAQs.…”
Section: Discussionmentioning
confidence: 99%
“…Intended to be the relationship health equivalent of the annual physical or dental checkup, the MC was designed to fill the gap in empirically supported relationship health care between tertiary care and preventative relationship education. The present study assesses the efficacy of the Marriage Checkup (Cordova, 2009; 2014; Cordova, Scott, Dorian, Mirgain, Yaeger, & Groot, 2005; Gee, Scott, Castellani, & Cordova, 2002; Morrill et al, 2011) as a brief, accessible maritalhealth intervention. The MC is a 2-session assessment and feedback intervention designed to be a safe and routine procedure for relationship health maintenance, early problem detection, and early intervention.…”
mentioning
confidence: 99%
“…Cordova, Warren, and Gee (2001) developed a Marriage Check-Up, which is designed for couples who may not be ready for couples therapy but who are experiencing distress. Improvements in marital satisfaction were generally maintained over two years (Gee, Scott, Castellani, & Cordova, 2002). Results from an open trial indicated that the treatment was acceptable to couples and that it attracted distressed couples.…”
mentioning
confidence: 89%